Biophysical methods in cell biology - Paluch, Ewa K. (London, UK Academic Press is an imprint of Elsevier, 2015)
This new volume of Methods in Cell Biology looks at methods for analyzing of biophysical methods in cell biology. Chapters cover such topics as AFM, traction force microscopy, digital holographic microscopy, single molecule imaging, video force microscopy and 3D multicolor super-resolution screening.--Provided by publisher.
Includes bibliographical references and index.
Keywords: Cytology -- Technique; Cell biology -- Methods; Biophysics -- Methods; Electronic books